First thing is to get rid of that darn "9" under the t. To do this, multiply everything on both sides by 9:
2 - t/9 = 11
9 * (2 - t/9) = 9 * 11
18 - t = 99
subtract 18 from both sides:
18 - t - 18 = 99 - 18
-t = 81
multiply both sides by -1:
-1 * -t = -1 * 81
t = -81
Double check your answer:
2 - t/9 = 11?
2 - (-81/9) = 11?
2 - (-9) = 11?
2 + 9 = 11? Yes! Therefore, correct!
2006-12-14 13:30:07
·
answer #1
·
answered by sep_n 3
·
0⤊
0⤋
2-t/9=11 move the 2 over and make its symbol opposite
-t/9=11-2 solve
-t/9=9 Multiply both sides by 9 to get t by itself
(-t/9)*9=9*9 sove
-t=81 Multiply both sides by -1
t=-81
i hope this has simplified it for you
2006-12-14 13:32:37
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
It's hard to tell whether it's (2-t)/9 or 2-(t/9)
If (2-t)/9
Multiply both sides by 9:
2-t=99
Subtract 2 from both sides:
-t=97
Multiply both sides by -1:
t=-97
If 2-(t/9)
Subtract 2 from both sides:
-t/9=9
Multiply both sides by 9:
-t=81
Multiply both sides by -1:
t=-81
2006-12-14 13:29:15
·
answer #3
·
answered by Joy M 7
·
0⤊
0⤋
2-t/9=11
Subtract 2:
-t/9=9
Multiply by -9:
t=-81
2006-12-14 13:28:46
·
answer #4
·
answered by Pascal 7
·
0⤊
0⤋
2 -t/9 = 11
-t/9 = 9
-t = 81
t = -81
2006-12-14 13:28:14
·
answer #5
·
answered by gabrielwyl 3
·
0⤊
0⤋
2-t/9=11
times all numbers in the equation with 9 to avoid fraction.
18-t=99
(- t)=99-18
t= (-81)#
2006-12-14 13:54:45
·
answer #6
·
answered by Tuhak 1
·
0⤊
0⤋
2 - (t / 9) = 11
First subtract 2 from both sides
- (t / 9) = 9
Now solve for t by multiplying by -9
- (t / 9) * 9 = 9 * -9
t = -81
2006-12-14 13:35:06
·
answer #7
·
answered by j 4
·
0⤊
0⤋
the main surprising answer demands which you preserve on with the regulations of mathematical operations. First, you would be able to desire to function what's interior the parenthesis, then multiply that by ability of what's outdoors, accompanied by ability of branch. So 6/2(a million+2) = 6/2(3) = 6/6 = a million
2016-12-11 09:23:48
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
2-t/9=11 u first add like terms and then divide by what u get and u basically get ur answer
2006-12-14 13:32:58
·
answer #9
·
answered by israel 1
·
0⤊
0⤋
- t/9=11-2
t/9= -9
t= -9 * 9
t = - 81
sorry! it didn't help to run spell check
2006-12-14 13:34:00
·
answer #10
·
answered by Piguy 4
·
0⤊
0⤋